The Development of Multilingual Thematic Digital Dictionary for Elementary School Students - Luh Parmawati; Ni Made Ratminingsih; I Gede Budasi (E-LINK JOURNAL, 2022)
In global competition, one of the most important assets that must be possessed is knowledge of literacy, which is needed to be able to grow into human resources that can compete globally. But unfortunately, children in Indonesia still have a relatively low level of awareness and literacy development. Therefore, the objective is to a multilingual thematic digital dictionary to assist students in developing their literacy skills. The method used is DnD (Design and Development). The subjects are elementary school students from nine schools in Buleleng Regency, Bali. The results showed that analysis of students' needs for learning media, a digital dictionary was developed, there were 5 steps and using PowerPoint. The final result was a digital dictionary consist of ten themes, equipped with picture, list of words and example of sentences in three languages (English-Bahasa Indonesia-Balinese), also audio. Therefore, this multilingual thematic digital dictionary categorized as an excellent medium for students.